Textilien (Herstellung, Verarbeitung, Handel) - Droß-Krüpe, Kerstin (RAC)

Ex India rediens hic fuit - Dokumentarische Quellen zu den Akteuren im römischen Rotmeerhandel von Augustus bis in die severische Zeit - Droß-Krüpe, Kerstin (Trade and Seafaring in Antiquity: Red Sea - Persian Gulf - Indian Ocean. Proceedings of the 1st Muziris Workshop, Trier, 28th May 2021)

Vertrag statt Vertrauen? Überlegungen zur Lehrlingsausbildung im frühkaiserzeitlichen Ägypten - Droß-Krüpe, Kerstin (Vertrauen als ökonomische Ressource in der antiken Marktwirtschaft)

Not Paying Taxes in Roman Egypt - Droß-Krüpe, Kerstin (Histories of Tax Evasion, Avoidance and Resistance)

Changing Identities at the Turn of the Common Era: The Case of Semiramis - Droß-Krüpe, Kerstin (Studia Orientalia Electronica)

Trade and Seafaring in Antiquity: Red Sea - Persian Gulf - Indian Ocean. Proceedings of the 1st Muziris Workshop Trier, 28th May 2021,

Orientalist Gazes. Reception and Construction of Images of the Ancient Near East since the 17th Century

#bedürfnisorientiert und #bindungsorientiert. Ein Erziehungstrend in den Sozialen Medien - Menzel, Tessa-Marie (Sozial Extra)

Theorielose Empirie? Ideen zu einem theoretisch sensibilisierten Forschen mit der Grounded Theory - Menzel, Tessa-Marie; Equit, Claudia (Qualitatives Forschen in der Erziehungswissenschaft. Prozesse und Vielfalt der rekonstruktiven Erkenntnisgewinnung)

When Do Firms Highlight Their Effective Tax Rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren (Accounting and Business Research)
This study examines GAAP effective tax rate (ETR) visibility as a distinct disclosure choice in firms’ financial statements. By applying a game-theory disclosure model for the voluntary disclosure strategies of firms, in a tax setting, we argue that firms face a trade-off in their ETR disclosure decisions. On the one hand, firms have an incentive to enhance their ETR disclosure when the ratio offers shareholders ‘favourable conditions’, for example, higher expected after-tax cash flows. On the other hand, the disclosure of a favourable low ETR could attract the attention of tax auditors and the public and ultimately result in disclosure costs. We empirically test disclosure behaviour by examining the relation between disclosure visibility and different ETR conditions that reflect different stakeholder-specific costs and benefits. While we find that unfavourable ETR conditions are not highlighted, we observe higher disclosure visibility for favourable ETRs (smooth, close to the industry average, and decreasing ETRs). Additional analyses reveal that this high visibility is characteristic of firm years with only moderately decreasing ETRs at usual ETR levels, while extreme ETRs are not highlighted. Interestingly and in contrast to our main results, a subsample of family firms does not seem to highlight favourable ETRs.

Der Wirtschaft auch in der Krise das Atmen erlauben, Pandemie und Ökonomie – Interview mit Steuerexpertin Caren Sureth-Sloane - Unterstell, Rembert (forschung - Das Magazin der Deutschen Forschungsgemeinschaft)

The Effect of Intellectual Property Boxes on Innovative Activity and Tax Benefits - Bornemann, Tobias; Kelley, Stacie; Osswald, Benjamin (Journal of the American Taxation Association)

Do Corporate Taxes Affect Executive Compensation? - Bornemann, Tobias; Jacob, Martin; Sailer, Mariana (The Accounting Review)

Losses Never Sleep – The Effect of Tax Loss Offset on Stock Market Returns during Economic Crises - Koch, Reinald; Holtmann, Svea; Giese, Henning (Journal of Business Economics)

Zusatzkosten der Besteuerung – Eine Analyse des steuerlichen Verwaltungsaufwands und der subjektiv wahrgenommenen Steuerbelastung - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Towards an Amended Arm´s Length Principle - Tackling Complexity and Implementing Destination Rules in Transfer Pricing - Greil, Stefan; Overesch, Michael; Rohlfing-Bastian, Anna; Schreiber, Ulrich; Sureth-Sloane, Caren (Intertax)

Wandel mit dem Stift gestalten - Ein exploratives Lehrformat zur Digitalen Transformation in einer mediatisierten Welt - Kückmann, Marie-Ann; Breuing, Friederike; Kundisch, Heike

Kurzfassung und interdisziplinäre Kommentierung der internationalen INCOG-2.0-Leitlinie „Kognitive Kommunikationsstörungen nach Schädelhirntrauma“ - Thoma, Patrizia; Quinting, Jana; Jonas, Kristina; Regenbrecht, Frank; Schumacher, Rahel; Büttner-Kunert, Julia (Zeitschrift für Neuropsychologie)
Zusammenfassung: Kognitive Kommunikationsstörungen (Cognitive Communication Disorders = CCDs) bezeichnen kommunikative Beeinträchtigungen, die v. a. die kommunikativ-pragmatischen Fähigkeiten betreffen und primär durch begleitende kognitive Störungen, z. B. der Gedächtnis-, Aufmerksamkeits-, und exekutiven Planungsfunktionen bedingt sind. Eine besondere Rolle spielen außerdem Beeinträchtigungen Sozialer Kognition (z. B. Empathie, Theory of Mind). Somit fällt die Diagnostik und Behandlung der CCDs interdisziplinär in den Zuständigkeitsbereich der Klinischen Neuropsychologie und der Sprachtherapie. Ein internationales, interdisziplinäres Netzwerk, die sog. INCOG-Arbeitsgruppe, hat im Jahre 2023 aktualisierte, evidenzbasierte Empfehlungen zur Diagnostik und Behandlung von CCDs und begleitender soziokognitiver Störungen spezifisch nach mittelschweren bis schweren Schädel-Hirn-Traumata veröffentlicht. Diese sollen im vorliegenden Artikel zusammenfassend vorgestellt und kommentiert werden. Es werden erste Vorschläge zur konkreten interdisziplinären Zusammenarbeit von Klinischer Neuropsychologie und Sprachtherapie abgeleitet.

A systematic approach to neurocognitive assessment for better detection and prevention of deficits in surgically treated brain tumours - Lucas, Carolin Weiß; Rodrian, Kimberley; Kochs, Sophia; Schultze-Rhonhof, Mira; Schroeter, Catharina; Becker, Maura; Nettekoven, Charlotte; Loução, Ricardo; Pieczewski, Julia; Jonas, Kristina; Kocher, Martin; Wiewrodt, Dorothee; et al. (Brain and Spine)

Ultra-short train TMS for more specific mapping of cortical language areas